1977
DOI: 10.1159/000260242
|View full text |Cite
|
Sign up to set email alerts
|

Human Saliva as a Nitrogen Source for Oral Streptococci

Abstract: The ability of human saliva supernatant to support the in vitro growth of Streptococcus mutans and Streptococcus sanguis was examined. Saliva supernatant could not serve as a sole source of energy, vitamins, minerals or accessory growth factors, but could serve as a source of organic nitrogen needed by the organisms for growth when tested in defined medium containing all nutrients except a nitrogen source. The greatest growth-promoting capacity of the saliva was found to be associated with the protein subfract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Most of the available evidence suggests that carbohydrates rather than nitrogen sources are the limiting nutrient for bacteria in dental plaque, although some controversy exists around this subject (12,21,44). However, during periods of dietary intake of carbohydrate, oral bacteria may experience nitrogen limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available evidence suggests that carbohydrates rather than nitrogen sources are the limiting nutrient for bacteria in dental plaque, although some controversy exists around this subject (12,21,44). However, during periods of dietary intake of carbohydrate, oral bacteria may experience nitrogen limitation.…”
Section: Discussionmentioning
confidence: 99%
“…On the morning of each day a test was performed, 20 ml of saliva, stimulated by chewing on a rubber band was collected and cen trifuged (10,000 g) to remove particulate matter. The 18 ml of supernatant was fractionated by ul trafiltration through an Amicon UM-10 mem brane (10,000 daltons) from which 3 ml of saliva protein concentrate (> 10,000 daltons) and 15 ml of saliva cluate were obtained as described by Cowman et al [1977].…”
Section: Salivamentioning
confidence: 99%
“…90, 5.33, 5.50, 5.58, 5.72, 5.80, 6.00 and 6.10 usually susceptible to alteration by S. mutans were seldom affected by the other oral streptococci. Growth attained by the oral streptococci in defined medium containing fractions of partially purified proteins was related to the presence or absence of proteins specifically altered by the organisms.Previous studies from this laboratory showed that strains of Streptococcus mutans and Streptococcus sanguis which were una ble to grow in a minimal basal medium could attain good growth if the medium was supplemented with clarified whole human saliva [Cowman et al, 1977], The growthpromoting capacity of the saliva was asso ciated with the protein portion obtained by fractional ultrafiltration. Comparison of electrophoretic patterns before and after growth of the organisms revealed the disap pearance of different protein bands, de pending on the strain of microorganism test ed, and in some cases the appearance of new protein bands, indicating that the mi croorganisms were interacting to different degrees with specific proteins from saliva [Cowman et al, 1976], The present study was undertaken to extend these studies to comparisons with two more common oral streptococci, Streptococcus salivarius and Streptococcus mitior, and to obtain further insight into the types of proteins which were specifically hydrolyzed and utilized for growth by the oral streptococci.…”
mentioning
confidence: 99%
“…Many oral bacteria, including streptococci, can use sali vary glycoproteins as nutrient sources [Cowman et al, 1977[Cowman et al, ,1979Carlsson, 1986], Though many oral bacteria can grow in human saliva [de Jong et al, 1984;van der Hoeven et al, 1989;Lumikari et al, 1991], the growth is evidently slower than under some in vitro conditions [Hillman et al, 1989]. Streptococcal cell production in saliva is carbohy ical and non-immunological antimicrobial agents that may interfere with microbial adherence, multiplication or me tabolism [Mandel, 1979;Tenovuo, 1989], These antimicro bial agents have a wide range of inhibitory effects in vitro [Tenovuo, 1989;Tenovuo and Lumikari, 1991], but no clear associations with plaque accumulation [Rudney et al, 1991], dental caries Tenovuo et al, 1987] or other oral diseases [Tenovuo and Anttonen, 1980;Lehtonen et al, 1984;Rudney and Smith, 1985;Brandtzaeg, 1989] have been found.…”
mentioning
confidence: 99%